Personal and Ambient Air Pollution Is Associated with Increased Exhaled Nitric Oxide in Children with Asthma - Delfino, Ralph J.; Norbert Staimer; Dan Gillen; Thomas Tjoa; Sioutas, Constantinos; Fung, Kochy; Steven C. George; Kleinman, Michael T. (Environmental health perspectives, 2006)
Background: Research has shown associations between pediatric asthma outcomes and airborne particulate matter (PM). The importance of particle components remains to be determined. Methods: We followed a panel of 45 schoolchildren with persistent asthma living in Southern California. Subjects were monitored over 10 days with offline fractional exhaled nitric oxide$(Fe_{NO})$, a biomarker of airway inflammation. Personal active sampler exposures included continuous particulate matter <$2.5 μ m$in aerodynamic diameter$(PM_{2.5})$, 24-hr PM2.5elemental and organic carbon (EC, OC), and 24-hr nitrogen dioxide. Ambient exposures included PM2.5, PM2.5EC and OC, and NO2. Data were analyzed with mixed models controlling for personal temperature, humidity and 10-day period. Results: The strongest positive associations were between$Fe_{NO}$and 2-day average pollutant concentrations. Per interquartile range pollutant increase, these were: for$24 μ g/m^3$personal PM2.5, 1.1 ppb$Fe_{NO}$[95% confidence interval (CI), 0.1-1.9]; for$0.6 μ g/m^3$personal EC, 0.7 ppb$Fe_{NO}$(95% CI, 0.3-1.1); for 17 ppb personal NO2, 1.6 ppb$Fe_{NO}$(95% CI, 0.4-2.8). Larger associations were found for ambient EC and smaller associations for ambient NO2. Ambient PM2.5and personal and ambient OC were significant only in subjects taking inhaled corticosteroids (ICS) alone. Subjects taking both ICS and antileukotrienes showed no significant associations. Distributed lag models showed personal PM2.5in the preceding 5 hr was associated with$Fe_{NO}$. In two-pollutant models, the most robust associations were for personal and ambient EC and NO2, and for personal but not ambient PM2.5. Conclusion: PM associations with airway inflammation in asthmatics may be missed using ambient particle mass, which may not sufficiently represent causal pollutant components from fossil fuel combustion.